AL-QUR’AN HADIS TENTANG PENDIDIKAN AKIDAH DAN AKHLAK - M Hadziq Azizi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to examine the basic concepts and practices of teaching religious beliefs and ethics based on the Qur’an and Hadith, while also assessing their contribution to shaping students’ character in a modern context. This study employs a qualitative approach with a phenomenological design to deeply explore how educators and students interpret the process of internalizing the values of faith and ethics within the madrasah environment. Data were collected through in-depth interviews, participant observation, and document analysis, involving faith and ethics teachers, school administrators, and students. The analysis process was conducted using the Miles and Huberman interactive model, which includes the stages of data reduction, data display, and verification of findings. This study reveals three key findings: (1) the understanding that education in faith and ethics is grounded in the concept of tawhid, as emphasized in Surah Luqman 31:13 and the example of the Prophet Muhammad (peace be upon him) in Surah Al-Ahzab 33:21; (2) educational practices that rely on exemplary behavior and habit formation have proven more effective in shaping students’ religious character; and (3) the implementation of moral education faces obstacles due to the strong influence of a secular and individualistic digital culture. Overall, this study underscores the need to integrate the cognitive, affective, and psychomotor domains in the application of faith and moral education. From a theoretical perspective, these findings reinforce the framework of Islamic education grounded in transcendental values, while from an empirical perspective, they provide guidance for curriculum development that emphasizes character building through exemplary conduct and the strengthening of the school’s religious culture. Future research is expected to test the effectiveness of this integrative model across various social and cultural contexts.